The Implementation of Contextual Teaching And Learning (CTL) in The 7th Grade English Class Within Merdeka Curriculum at SMP Negeri 5 Tulungagung - Juliane Rifqi Vandita; Moh Choirul Huda (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study aims to the implementation of Contextual Teaching and Learning (CTL) learning conducted and applied by teachers in the seventh grade English subject at SMP Negeri 5 Tulungagung. The subject of this research is the seventh grade students of SMP Negeri 5 Tulungagung. The object of this research is the implementation of Contextual Teaching and Learning (CTL) learning in English subjects. Data collection techniques were observation and interview. Data analysis used qualitative analysis and to check the validity of the data using triangulation techniques. This research is included in qualitative research. The results showed that the implementation of Contextual Teaching and Learning (CTL) applied by teachers in seventh grade English subjects at SMP Negeri 5 Tulungagung has been going well. In the learning process in class, teachers always start by providing stimulation and motivation to learn. Forming class groups carried out by the teacher makes students more active and not quickly bored in following the learning process. In the learning process, students are also given games and interactive learning media to motivate them to always be enthusiastic about learning.